Manejo de malezas con herbicidas bipiridilos y triazinas interaccionados con fertilizantes químicos, utilizando labranza mínima en el cultivo de maíz - Triviño Quinto, Eduardo Rafael (2017)
VIII. SUMMARY The present experimental work was developed in the lands of Dr. Jonathan Coello Aguilar, belonging to Rcto. Campo Alegre del Cantón baba, Province of Los Ríos. The geographic coordinates are 790 32 'west longitude, 010 49' south latitude and 8 m high. The soil is frank clay, with regular topography. Seeds of hybrid corn "Dekalb 7088" were used as genetic seed material. The treatments were conformed by different doses of herbicides such as Paraquat (2.0 and 2.5 L / ha); Diquat (2.0 and 2.5 L / ha); Atrazine (1.0 and 1.5 kg / ha) and sub-treatments by fertilization levels of 160 kg / ha of N + 40 kg / ha of P2O5 + 80 kg / ha of K2O; 120 kg / ha of N + 20 kg / ha of P2O5 + 60 kg / ha of K2O and 90 kg / ha of N + 30 kg / ha of K2O. The experimental design called "Split Parcels" was used, with six treatments, three sub-treatments and three replicates. Comparisons of means of treatment and sub-treatment were performed using the Duncan test at 5% probability. All agricultural practices required to grow maize for normal development, such as field preparation, planting, weed control, irrigation, fertilization, insect-pest control and disease and harvesting were performed. To estimate the effects of treatments and sub-treatments, herbicide selectivity data were evaluated at 7 and 14 days, weed control at 14 and 21 days after application of herbicides, plant height, length and diameter Of ear, number of grains per ear, weight of 1000 grains, yield and economic analysis. From the results obtained in the present investigation, it was determined that in the selectivity of the products, Paraquat and Diquat, both in doses of 2.5 L / ha caused little damage to the 7 days after the application of the herbicides, decreasing The 14 days; The best weed control at 14 and 21 days was obtained with the applications of Paraquat in doses of 2.5 L / ha and Atrazine in doses of 1.5 kg / ha; Higher plant height was recorded using Atrazine 1.5 kg / ha with fertilization of 120 kg / ha of N + 20 kg / ha of P2O5 + 60 kg / ha of K2O; In the length and diameter of ear, higher results were obtained with the use of Paraquat 2.5 L / ha using low fertilization level of 90 kg / ha of N + 30 kg / ha of K2O; The highest number of grains per ear was reported with the application of Diquat 2,5 L / ha with 90 kg / ha of N + 30 kg / ha of K2O, while the weight of 1000 grains stood out with the use of Atrazine 1, 0 kg / ha with 120 kg / ha of N + 20 kg / ha of P2O5 + 60 kg / ha of K2O and the highest crop yield and net benefit was achieved by the use of Atrazine 1.0 kg / ha with fertilization level Of 120 kg / ha of N + 20 kg / ha of P2O5 + 60 kg / ha of K2O with 6621.6 kg / ha and $ 606.48, respectively.